Influence Of Internal Control System Weaknesses And Audit Quality On The Quality Of Local Government Financial Reports In Indonesia With Good Government Governance As Moderating - Pakpahan, Ramses; Murwaningsari, Etty; Mayangsari, Sekar (International Journal of Science, Technology & Management, 2022)
The purpose of this study is to investigate the impact of internal control system weaknesses and audit quality on the quality of financial reports in district and city governments in Indonesia, using Good Government Governance as a moderating variable. The Partial Least Squares-SmartPLS analytic approach is used in this study, which includes data from 2,155 observations from 508 district and municipal administrations in Indonesia since the implementation of the accrual-based accounting system from 2015 to 2019. The findings of this study show that (1) internal control system weaknesses have a positive and significant effect on the quality of local government financial reports; (2) audit quality has a positive and significant effect on the quality of local government financial reports; (3) good government governance can weaken the relationship between internal control system weaknesses and the quality of local government financial reports; and (4) good government governance can weaken the relationship between internal control system weaknesses and the quality of local government financial reports. This study sheds new light on the relationship between internal control system weaknesses and the quality of public sector audits since the adoption of the accrual-based accounting system, as well as the quality of local government financial reports, with Good Government Governance acting as a moderator.